Understanding Management Practices of Selected Credit Cooperatives in Cavite: A Microanalysis Study - Del Rosario, Christine Lloyd E.; Mendrez, Jayven Gianne D.; Abug, Nerisa B. (Future Science / FSH-PH Publications, 2023)
The researchers conducted this study focusing on credit cooperatives, which are common in the community. The study aimed to determine the participants' business profile in terms of length of operation and number of members. It also aimed to determine the management practices and the challenges encountered by the participants in terms of planning, commanding, coordinating, and, controlling. The study used a descriptive method, and purposive sampling comprised participants in Cavite. The findings revealed that most participants have been operating above 20 years and have over 500 members. The management practices of most participants formulate a plan based on the resources available and have a flexible, continuous, relevant, and accurate method of their cooperative. Moreover, the participants supervised their members and motivated them to achieve their goals, adhere to policies, and treat them according to cooperative standards. Most of the participants hold meetings addressing matters of common interest. Lastly, most participants ensure that the cooperative activities align with its policies and objectives. The challenges encountered by the participants were developing a short-term plan and experiencing failure despite having a good plan. Most participants needed clarification, commands, and instructions. Finally, most participants have had trouble in knowing the weaknesses of its cooperative and often experienced dynamic plans. Moreover, the researchers provide solutions to address the participant's challenges.